Mechanism of formation of space-charge polarization in dielectrics - Medvedev, V. Ya.; Kuketaev, T. A.; Tonronogov, M. P. (Kluwer Academic Publishers-Consultants Bureau, 2006)
A general mechanism of space-charge relaxation in dielectrics, whose separate manifestations were studied in [5–7], is investigated. A strict solution of a system of the nonlinear Fokker-Planck and Poisson equations has been derived in the form of a Fourier series; a recurrent relation is suggested for the oscillation modes which allows the mechanism of space-charge relaxation to be considered as an interaction of modes generated in crystals in an external electric field. Very cumbersome calculations do not allow us to estimate the opportunity of technical applications of the solution obtained within the framework of one paper.